Fee charging in Nigerian academic libraries: what justification (1993)
This paper examines the issue of charging as it affects Nigerian academic libraries. The issue is looked at from the economic, socio-cultural and political viewpoints. Because of its complexity from the three perspectives mentioned aboved, it was concluded that while generalized library services could be made free, charging can be introduced for personalised library services and information services. However, a clear distinction must be made between these three categories of services.